Cuidados culturales e integrales aplicados a niños con desnutrición menores de 4 años. CDI Guaranga. parroquia Simiatug. periodo diciembre 2022 – abril 2023 - Veloz Trujillo, Alvaro Israel (2023)
The purpose of this research was to determine the cultural and comprehensive care applied to children with malnutrition under 4 years of age, CDI Guaranga, Simiatug parish, began with an approach and formulation of the problem, which allowed formulating, justifying and stating the objectives of this work. investigative. Next, a theoretical framework was presented with the content of research background, theoretical bases and definition of terms, which allowed a proper study of the variables raised. Consequently, the relevant methodology was determined, which included a quantitative and descriptive approach. Therefore, the information was collected by applying a survey to the mothers of the children who attend the Child Development Center. The results showed that boys and girls have a lack of sufficient nutritious food, a lack of knowledge about nutrition and a lack of economic resources to acquire adequate food, in such a way that there is a need to develop a food guide with the essential components. in food and nutrition for the Guaranga Child Development Center. Finally, the food guide is presented with the essential components in child feeding and nutrition, which were of great help and provided sufficient support to promote medical care and value cultural practices in the comprehensive care of children with malnutrition, thus allowing, reduce the risk of child malnutrition, while creating awareness among children, mothers and staff who work in the institution. Keywords: Cultural Care, Comprehensive Care, Malnutrition Infant, Food.